The Author's Ethical Responsibility and the Ethics of Reading. Issue 1 (April 2018) - Lothe, Jakob
Abstract : Inspired by Ranjan Ghosh and J. Hillis Miller's intervention in Reading Literature across Continents, this essay discusses the narrative ethics of two narratives: Olga Horak's first-person narrative from the Holocaust and W. G. Sebald's novel Austerlitz (2001). While Sebald is an internationally acclaimed author, Horak is a Holocaust survivor whose story, orally transmitted to the author of the essay in Sydney in 2013, is presented as written text in Time's Witnesses: Women's Voices from the Holocaust (2017). Even though these narratives are very different, the essay argues that both are possessed of a strong ethical dimension that not only highlights the authors' sense of ethical responsibility, but also that of the reader. This article argues that, first, even in narratives as different as these two, the author's sense of ethical responsibility is closely linked to the reader's ethical obligation; second, as an integral part of the reader's interest in and engagement with the narrative text, this kind of obligation is generated and shaped by the narrative as textual structure; and, third, two of the most important constituent elements of this kind of form – that is, elements of narrative form possessed of a distinctly ethical dimension – are narrator(s) and characters, and the interplay of both with the author on the one hand and the reader on the other. In order to support the argument, the essay discusses a selection of illustrative examples from both narratives.